2005
DOI: 10.1002/mrm.20355
|View full text |Cite
|
Sign up to set email alerts
|

Imaging anisotropic and viscous properties of breast tissue by magnetic resonance‐elastography

Abstract: MR-elastography is a new technique

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
315
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(319 citation statements)
references
References 26 publications
2
315
0
2
Order By: Relevance
“…For reducing noise, numerical derivatives were calculated by 3D gradients according to Anderssen and Hegland [29] using a twopixel symmetric window in three dimensions [30]. The resulting strain components of the wave field (derivatives of the three Cartesian components of the displacement field) were used to calculate the curl field, as has been established in 3D MRE for suppressing volumetric strain [31]. The curl components C 1 , C 2 and C 3 are defined as follows: Fig.…”
Section: Data Processingmentioning
confidence: 99%
“…For reducing noise, numerical derivatives were calculated by 3D gradients according to Anderssen and Hegland [29] using a twopixel symmetric window in three dimensions [30]. The resulting strain components of the wave field (derivatives of the three Cartesian components of the displacement field) were used to calculate the curl field, as has been established in 3D MRE for suppressing volumetric strain [31]. The curl components C 1 , C 2 and C 3 are defined as follows: Fig.…”
Section: Data Processingmentioning
confidence: 99%
“…MRE provides quantitative stiffness information and enables, in a way, palpation by imaging, even of deep-lying tissues. Several studies have shown the potential of MRE for quantitatively depicting the elastic properties of breast tissue in vivo, and have revealed high shear elasticity in breast tumor tissue and a remarkably large dynamic range to discriminate benign from malignant lesions (179)(180)(181)(182).…”
Section: Mri Elastography and The Mechanical Properties Of Musclementioning
confidence: 99%
“…Thus, the plane of symmetry is spanned by the x-and z-axes, which define the corresponding axial elastic moduli (Young's moduli) E 1 ϭ E 2 and E 3 . The principal axis of symmetry (z) is assumed to be aligned with the long axis of the muscle so that it is parallel to the muscle fibers (12,24,27,30).…”
Section: Shear Waves In Transverse Isotropic Elastic and Incompressibmentioning
confidence: 99%